Respuesta :
Explicación paso a paso:
[tex]a. \: \: \: \frac{1}{ {b}^{ - 2} } = {b}^{2} [/tex]
[tex]b. \: \: \: \frac{2}{ {x}^{ - 4} } = {2x}^{4} [/tex]
[tex]c. \: \: \: \frac{ {a}^{ - 25} }{ {b}^{ - 10} } = \frac{ {b}^{10} }{ { {a}^{25} }^{} } [/tex]
[tex]d. \: \: \: \frac{ {5}^{ - 2} }{ {2}^{ - 5} } = \frac{ {2}^{5} }{ {5}^{2} } [/tex]
[tex]e. \: \: \: \: \frac{ {5a}^{ - 4} }{ {2b}^{ - 8} } = \frac{ {2b}^{8} }{ {5a}^{4} } [/tex]
[tex]f. \: \: \: \frac{ {x}^{ - 12} }{ {5b}^{ - 9} } = \frac{ {5b}^{9} }{ {x}^{12} } [/tex]